Magic Tree House, Merlin Mission: A Perfect Time for Pandas - Book 48 (20) Book 20 (Merlin Missions) and Book 48 (Magic Tree House) - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2012)
Magically transported to southwest China to find the final object needed to break the spell on the wizard Merlins beloved penguin, Jack and Annie take a side trip to the worlds largest giant panda reserve.
Keywords: Magic -- Juvenile fiction; Space and time -- Juvenile fiction; Giant panda -- Juvenile fiction; Pandas -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; China -- Juvenile fiction